2012
DOI: 10.1148/radiol.12112532
|View full text |Cite
|
Sign up to set email alerts
|

Interplatform Reproducibility of CT Coronary Calcium Scoring Software

Abstract: While mere numeric values might be different, commercially available software platforms produce comparable CAC scoring results, which suggests a vendor-independence of the method; however, none of the analyzed software platforms appears to provide a distinct advantage for risk stratification, as the variability of CAC scores depending on the reconstruction interval persists across platforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…With the clinically used CCS protocols, CCS were acquired with routine CT manufacturers' software. However, it was demonstrated by Weininger et al that different types of CCS scoring software resulted in similar CCS [22].…”
Section: Discussionmentioning
confidence: 99%
“…With the clinically used CCS protocols, CCS were acquired with routine CT manufacturers' software. However, it was demonstrated by Weininger et al that different types of CCS scoring software resulted in similar CCS [22].…”
Section: Discussionmentioning
confidence: 99%
“…17 Another study observed that CAC score did not differ materially according to different protocols and/or workstations, thus, highlighting the ease of access in obtaining CAC measurements irrespective of the type of scanner used. 27, 28 This study is not without limitations. Although the Korean and US cohorts were large in sample size, both may not be truly representative of general populations in South Korea and the USA, respectively.…”
Section: Cac Vs Age and Gendermentioning
confidence: 90%
“…A standard reference was obtained with a semi-automatic, previously validated [16], post-processing software (syngo.via, Siemens Healthineers). All 315 CSCT scans were double read by two radiologists in at least two sessions (M.S.…”
Section: Data Reportingmentioning
confidence: 99%